MATERIALS ANALYSIS OF THE ENGLISH TEXTBOOK FOR THE TENTH GRADE STUDENTS IN INDONESIAN ELT CONTEXT - Setyawati, Yulia Fida; Fitriani, Ulwi Ajeng (Transpublika Publisher, 2023)
Selecting course books involves matching the material with course objectives and learners' needs. This study examined the “Bahasa Inggris SMA/MA/SMK/SMAK Kelas X Semester 1 English” textbook material using the McGrath, Cunningsworth, and National Education Standards Agency (BNSP) guidelines to develop an appropriate standard for a textbook evaluation. The blueprint of material evaluation consists of three major stages: pre-evaluation, evaluation, and post-evaluation. The level of compliance was divided into three categories: Yes (= 2 points), No (= 0 points), and Partly (1 point) for the purposes of tabulation and statistical data analysis. This simplified the discussion of the results by allowing a raw score of 0 to 2 for each of the categories examined. The research demonstrates that the textbook is appropriate for use as a teaching tool. The results suggest that there are some highlights for the material evaluation. The provided activities ought to be well-rounded enough to grab the students' interests. Incorporating genuine texts from actual settings can offer students a true immersion in authentic spoken language, aiding them in effectively practicing language skills for real-life communication. It is important to include representations of gender equality and diverse ethnic groups to cater to the needs of students from various cultural and linguistic backgrounds.